Design of Internet of Things (IoT) Based Hydroponic Controlling Device in Pyramid Greenhouse - Arif Umami; Bagus Muhammad Akbar (Techno LPPM, 2022)
Smart farming technology was previously implemented at Wedomartani experimental station, Faculty of Agriculture UPN "Veteran" Yogyakarta. It is proven to overcome human resource limitations in hydroponic cultivation. Even so, Smart farming has not been implemented yet in Pyramid Greenhouse, Which is the iconic landmark of the Faculty of Agriculture. Preparing IoT-based devices requires designs with certain specifications. Without an appropriate design, it would be found a failure system. This article’s purpose was to design an Internet of things (IoT) based hydroponic controlling device in Greenhouse Pyramid UPN “Veteran” Yogyakarta. It was built based on a literature study. Expert proofing was performed to ensure the design would work if implemented. The design contained the system overview, hardware description, user interface design, and integration of device system design in hydroponic installations. The design was positively accepted by users (Head of the experimental field and technicians). In the future, the proposed design needs to be realized as a part of greenhouse development.